Post-occupancy evaluation: Identifying and mitigating implementation barriers to reduce environmental impact. (10th November 2022) - Roberts, C.J.; Edwards, D.J.
Abstract: Post-occupancy evaluation (POE) enables designers and contractors to determine whether a building's performance 'in-use' meets the specifications prescribed 'in-design'. Hence, POE presents an invaluable opportunity for stakeholders within the architecture, engineering, construction and operations (AECO) sector to learn from mistakes and improve the environmental performance of future designs. Against this contextual backdrop, this paper identifies the barriers to performing a POE implementation following a building's hand-over and use, and how these barriers inadvertently prevent sustainable development goals from being reached. A theoretical model is developed which enables building owners and users to implement a POE and thereby realise its innate potential to reduce the impact of the built environment upon the natural environment. An interpretivist philosophical stance is adopted to analyse both secondary and primary data collated using a three-stage waterfall process. First, a thematic content analysis is conducted utilising the transcript of a practitioner focus group convened to garner perspectives on the prominent barriers to POE implementation. Second, a scientometric analysis is undertaken to examine the prevailing body of knowledge (BoK) pertaining to sustainability, circular economy and barriers to POE implementation. Finally, a cross-comparative analysis of the emergent findings emanating from the previous two stages is conducted to ascertain whether academic literature is addressing the barriers identified by industry practitioners. The research reveals that despite the significant opportunities that POE presents to reduce the built environment's substantial impact upon the natural environment, only a relatively small proportion of the POE BoK explores this objective. Similarly, an even smaller proportion of literature examines the barriers to POE implementation and how to overcome them. The cross-comparative analysis undertaken highlights inconsistencies between practitioner requirements regarding implementation barriers and the proportion of the POE BoK pursuing this objective. Curiously, there is no literature delineating POE's potential to facilitate a circular economy within the built environment sector. A novel theoretical model emerges from this research which acts to bridge a gap between theory and practice and provides utility for researchers and practitioners alike to increase the interchange of knowledge pertaining to pertinent POE requirements. The resultant model establishes POE as a crucial environmental feedback mechanism for stakeholders within the AECO sector.